Idiopathic ketotic hypoglycemia in children: an update - Kotb Abbass Metwalley; Hekma Saad Farghaly (Korean Society of Pediatric Endocrinology, 2024)
Idiopathic ketotic hypoglycemia (IKH) is defined as bouts of hypoglycemia with increased blood or urine ketones in certain children after prolonged fasting or during illness. IKH is divided into physiological IKH, which is most frequently observed in normal children with intercurrent acute illness, and pathological IKH, which occurs in children who lack counter-regulatory hormones, have a metabolic disease, or have Silver-Russell syndrome. The typical patient is a young child between the ages of 10 months and 6 years. Episodes nearly always occur in the morning after overnight fasting. Symptoms include those of neuroglycopenia, ketosis, or both. IKH may be diagnosed after ruling out various metabolic and hormonal conditions associated with ketotic hypoglycemia. Sufficient amounts of carbohydrates and protein, avoidance of prolonged fasting, and increased frequency of food ingestion are the main modes of treating IKH. It is crucial to understand the pathogenesis of IKH and to distinguish physiological IKH from pathological IKH. In this mini-review, we present a brief summary of IKH in terms of its definition, types, clinical presentation, diagnosis, and therapeutic approach in children.